Application of Instruments of Fiscal Policy in Nepal - Acharya, Krishna (Economic Review of Nepal, 2019)
Fiscal policy is an important component of government policy to bring high, broad based and sustainable economic development. Budget, taxation, public expenditure and public debt are the instruments of fiscal policy and these instruments are not using appropriately, effectively and efficiently in the context of least developed countries so that they trapped as a low-income nation. In Nepalese context, government of three-layer formulating and implementing budget to mobilize national, provincial and local level resources and to follow the norms of decentralization. The ratio of capital expenditure in relation to recurrent expenditure is high indicator of low economic development in the coming years. In eleven months of fiscal year, only 50 percent of the development expenditure can utilize is the symbol of gloomy situation of our economy. Regarding to tax base and rate, it has some regressive nature so that collection of tax became difficult task. People are interested to evasive tax due to administrative hurdles and its poor utilization policy. Resources can divert into productive sector due to better public expenditure policy. Government of Nepal can utilize the resources of its citizen on the basis of the trust of government. Ultimately better fiscal policy can pave the way for higher, sustainable and broad-based economic growth rate. We can graduate our nation in the list of developing nation by 2030 as well as can fulfill sustainable development goals.